The Relationship of Maternal Knowledge and Attitude with Basic Immunization Equipment in the Working Area of The Akung City Bandar Lampung Health Center in 2023 - Ria Mustika; Aprina Murhan; Riska Wandini (STIKES Adi Husada, 2023)
Immunization is an important thing to increase the immunity of children's immunity to various diseases. To determine the relationship of knowledge and attitudes of mothers with the completeness of basic immunization in infants aged 1 year in the working area of the Bakung Bandar Lampung Health Center. This type of research is analytical with cross sectional design. The sample in this study is a mother with a child aged 1 year who lives in the Working Area of the Daffodil Health Center. Sampling techniques in research using simple random sampling techniques. The dependent variable in the study is the completeness of basic immunization and the independent variable in the study is the knowledge and attitude of the mother. The results showed that there is a significant relationship of maternal knowledge with basic immunization (p value= 0.000) and there is a significant relationship of maternal attitudes with basic immunization (p value= 0.000) in children aged 1 year in the Working Area of the Daffodil Health Center. Researchers expect health workers and health facilities to be able to provide clear information about immunization, so that there is no false information received by the public. And it is also expected that all mothers can provide complete basic immunization to their children.